Feminismer och feminissanser: Britt-Ingrid Persson (BIP), Barbro Bäckström och 1970-talet i feministisk konsthistorieskrivning - Sjöholm Skrubbe, Jessica (Passage - Tidsskrift for litteratur og kritik, 2025)
“Feminisms and Feminaissances: Britt-Ingrid Persson (BIP), Barbro Bäckström, and the 1970s in Feminist Art History" This article explores sculptures by Swedish artists Britt-Ingrid Persson (BIP) and Barbro Bäckström in relation to the historiography of feminist art. It argues that the artworks both belong to and transcend the feminist 1970s and that their anachro- nistic agency allows for transtemporal narratives that challenge linear conceptuali- sations of time.